An advanced cervical ectopic pregnancy - Celik, Ebru; Kavak, Salih Burcin; Ilhan, Rasit; Kaplan, Selcuk; Arat, Ozgur; Sapmaz, Ekrem (Walter de Gruyter Gmbh, 2015)
The aim of this paper is sharing our experience in an advanced cervical ectopic pregnancy (CEP), which is managed by conservative surgery. We herein report a case of a 24-week pregnant woman with CEP. She was first referred to a tertiary center due to early starting intrauterine growth retardation and oligohydramniosis. Surgery was planned as soon as the diagnosis of CEP was made. By taking measures to reduce bleeding, conservative surgery was succesfully performed, and a hysterectomy was avoided. The fertility of the patient was preserved. The possibilty of CEP must be always be kept in mind, and the exact localization of the gestational sac must be determined in all patients. In advanced pregnancies, ultrasonographic examination must not only focus on examination of the fetus but also focus on the examination of contours of the uterus. These will give us the chance to diagnose CEP as soon as possible and reduce morbidity and mortality.
Keywords: Cervical ectopic pregnancy; intrauterine growth retardation; second trimester